2016
DOI: 10.1016/j.clml.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Renal Failure on Correlation and Concordance Between 2 Free Light Chain Assays

Abstract: Despite adjusted reference ranges for Freelite FLC ratio, there are approximately 12.5% discrepancies in interpretation of FLC ratio between the 2 available assays. They are not linked to renal failure stage and neither of the assays performed better than the other: results must be interpreted taking into account clinical data and the same assay must be used for patient follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In addition, measurement of sFLCs can be determined by any of the following three methods: absolute level of involved sFLC, ratio of involved to uninvolved sFLCs, and difference between involved and uninvolved sFLCs 11,19,20 which contributes to the variability of testing and clinical interpretation of the results. Furthermore, a substantial percentage of MM patients with impairment of renal function display elevated sFLCs from causes unrelated to MM, precluding an accurate clinical assessment of their disease status 21–23 . Thus, the limitations of the two most widely used tests for monitoring MM patients demonstrate the need for developing new assays that can be easily performed and are more accurate and faster at identifying changes in their clinical status and predicting their outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, measurement of sFLCs can be determined by any of the following three methods: absolute level of involved sFLC, ratio of involved to uninvolved sFLCs, and difference between involved and uninvolved sFLCs 11,19,20 which contributes to the variability of testing and clinical interpretation of the results. Furthermore, a substantial percentage of MM patients with impairment of renal function display elevated sFLCs from causes unrelated to MM, precluding an accurate clinical assessment of their disease status 21–23 . Thus, the limitations of the two most widely used tests for monitoring MM patients demonstrate the need for developing new assays that can be easily performed and are more accurate and faster at identifying changes in their clinical status and predicting their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a substantial percentage of MM patients with impairment of renal function display elevated sFLCs from causes unrelated to MM, precluding an accurate clinical assessment of their disease status. [21][22][23] Thus, the limitations of the two most widely used tests for monitoring MM patients demonstrate the need for developing new assays that can be easily performed and are more accurate and faster at identifying changes in their clinical status and predicting their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 To this date, direct comparison of serum FLC concentrations measured using the 2 available assays at the patient level in patients with mild-to-moderate CKD are scarce. [10][11][12] Jacobs et al 10 have reported a comparison of the 2 available assays in 284 patients with varying degrees of CKD, including mild-to-moderate kidney dysfunction.…”
mentioning
confidence: 99%
“…Indeed, the use of a kappa/lambda sFLC ratio appears to be a more sensitive marker of monoclonal FLC production than the absolute sFLC concentration, because the interpretation incorporates the suppression of the nontumor sFLC. Moreover, the nephelometric/turbidimetric assays present numerous technical limitations: lot-to-lot variations, antigen excess, nonlinear responses especially at higher dilution, poor post-dilution linearity, detection and quantification of oligomerization of monoclonal sFLC, gap in quantification, under and overestimation with extreme values, a huge heterogeneity in FLC measurements illustrated in pairwise comparison with external quality controls, different results on the same samples according to the analytical platform used, and the reference ranges for the Freelite ® test being dependent on the analytical platform (8,9). Regarding the Sebia FLC assay, technical experience reveals that several analytical improvements such as dilutions need to be made (10).…”
mentioning
confidence: 99%
“…Numerous discrepancies between tests have been documented for patients especially with chronic kidney disease and AL amyloidosis. For example, while an extended kappa/lambda sFLC ratio has been proposed for patients with chronic kidney disease when the sFLC are evaluated with the Freelite ® assay (13), this is not a requirement with the N Latex assay (8,14,15). But with a worsening of renal function, the Sebia Free Light Chain Assay detected an increase in both serum kappa and lambda FLC, and an increase in the kappa/lambda sFLC ratio (16).…”
mentioning
confidence: 99%